Factors Influencing Students' Higher Education: Marketing, Fees, Word of Mouth - Agustiawan Djoko Baruno; Sri Utami Ady; Garry Brumadyadisty (Journal of Research in Social Science and Humanities, 2024)
This study investigates the influence of digital marketing, tuition fees, and word-of-mouth (WOM) promotion on students' decision to choose the Faculty of Economics and Business at Dr Soetomo University. This multi-faceted decision-making process is shaped by various factors, including the interaction between digital marketing efforts, tuition fees, and WOM promotions. This study aims to understand how these factors interact and influence student choice. Using a cross-sectional survey design, data was collected from 100 undergraduate students from the Faculty of Economics and Business at Dr Soetomo University. Data was collected using a structured questionnaire distributed online via Google Forms. The results showed that digital marketing alone did not significantly influence students' decision to choose Unitomo. However, tuition fees and WOM have a significant partial impact on student choice. In addition, when considered together, digital marketing, tuition fees, and WOM significantly influence the decision-making process. The most dominant factor influencing students' decision is tuition fees. The implications of these findings suggest that while digital marketing needs to be optimised, conventional methods and word of mouth remain important in influencing student decisions. Universities should consider integrating effective digital marketing strategies with strong word-of-mouth campaigns to enhance their recruitment efforts. This study contributes valuable insights for higher education marketers and policy makers who aim to attract and retain students effectively.